Fabrica Societatis. No. 1/2018 : Spis treści (Instytut Socjologii Uniwersytetu Wrocławskiego, 2018)
Fabrica Societatis is a scholarly journal that answers the growing need in sociology for the research topics related to activities participating in the creation of social worlds and for works on the everyday existence of people. The main goal of the journal is to create space for theoretical, methodological and empirical enquiries, aiming at discovering everyday procedures creating and shaping various manifestations of social life. It is also a place to publish articles that appreciate the uniqueness of human experience and that change perspectives so as to go out of the social box. Such attempts often require search rather than ready answers. Therefore, our journal is open to both works of experienced researchers and works of young scholars who have just begun their career, as well as to finished projects, working papers, and voices giving chance to enrich sociological knowledge and open interdisciplinary horizons. The first issue of the journal is divided into five sections. Two of them are of a thematic nature: one is devoted to dress and dressing up understood as a process that co-creates a subject and the subject’s relation with his or her environment, whereas the other is devoted to present issues of migration and identity. The third section, “Inspirations”, comprises of three articles that are not strictly sociological, yet they interestingly take up the issues relating to social world and everyday practices. The fourth section (“Debuts”) presents scientific achievements of persons that begin their career. The last section (“Miscellanea”) comprises two publications calling for the necessity to investigate closely significant issues in the field of gender studies, and management.
Keywords: everyday reality; everyday life; dress and dressing up; migrations; identities; gender studies; organisational culture